The Impact of Terroir’s Perceived Image on The Consumer’s Attitude Regarding Terroir Products: Case of Chefchaouen’s Terroir Products - Oualid HARRASSE (Communications of International Proceedings, 2024)
The researchers and marketing specialists are aware of the importance of understanding attitudes in order to unravel the psychological processes that drive consumer choices. The aim of this article to explore the consumer’s attitudes regarding Chefchaouen Terroir’s products while focusing on aspects related to Terroir’s perceived image such as artisanal production, the reference to local culture and history, as well as the importance of origin and savoir-faire. A survey was conducted among 297 consumers in order to understand the impact of Terroir’s perceived image on consumer’s attitude regarding Chefchaouen Terroir products. The face to face questionnaire is used as method of data collection. The results demonstrate that Terroir’s perceived image has a positive impact on consumer’s attitudes, a mostly positive perception of Terroir’s products, with a strong valorization of origin and savoir-faire.
Keywords: Terroir; Terroir products; consumer attitude; Terroir’s perceived image.